High heel shoes with adjustable height of the heel. Issue 1 (December 2020) - Kumar, Naveen; Panda, Surya Narayan; Kaushal, Rajesh Kumar
Abstract: High heel shoes have been worn by women since a long time especially in western culture. Like clothing, high heel shoes are also categorizing as one of the personality symbol. Therefore, it is a necessary part of every woman's closet. The main objective of the present invention is to disclose a shoe with an automatic adjustable heel using a quite simple and less complex arrangement for adjusting heel height wherein the same is configured to be operated from mobile application. The present literature suggests that the design of the existing solutions is complex. It has been also found from the literature review that wearing high heel shoes for a long duration have certain side effects. Therefore, high heel shoes are worn occasionally. This paper presents the design of an adjustable height of a high heel shoe by using a mobile application as per requirement of the user. A mini screw-jack arrangement connected with a motor unit is placed within a defined heel area. Thus, the dual functionality of the shoe allows women to wear it on special occasion like parties as well as in casual.